circPTPN12 promotes the progression and sunitinib resistance of renal cancer via hnRNPM/IL-6/STAT3 pathway - Yi Shou; Changjie Yue; Qi Wang; Jingchong Liu; Jiaju Xu; Qi Miao; Di Liu; Hongmei Yang; Yuenan Liu; Xiaoping Zhang (Cell Death and Disease, 2023)
Abstract Renal cell carcinoma (RCC) is characterized by the difficulties in early diagnosis and the propensity to metastases. For advanced RCC, sunitinib targeted therapy is the clinically recommended first-line drug and the major challenge of sunitinib treatment is adaptive resistance. Therefore, it is imperative to research the mechanisms underlying sunitinib resistance. In this study, we discovered that circPTPN12 was highly expressed in RCC tissues and was associated with poorer clinical outcomes. circPTPN12 could promote the proliferation, migration, invasion, and sunitinib resistance of RCC cells. Mechanistically, circPTPN12 was found to form a complex with hnRNPM, which was involved in the regulation of mRNA processing. The combination with circPTPN12 enhanced the ability of hnRNPM to maintain the stability of IL-6 mRNA and further activated the STAT3 signaling pathway. The study revealed that circPTPN12/hnRNPM/IL-6/STAT3 axis promoted RCC progression and sunitinib resistance, which might be a promising therapeutic target for relieving sunitinib resistance in RCC.